Peppers, ports and pest tracking - Clarke-Harris, Dionne (Technical Centre for Agricultural and Rural Cooperation, 2006)
With the hot pepper market heating up, Jamaica has developed a state-of-the-art pest-incidence traceability system to ensure the gall midge and other pests do not become a barrier to North American and European market access.